2017
DOI: 10.1177/0022034517712435
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Induces Immunosuppression by Upregulating PD-1/PD-L1 in HNSCC

Abstract: Head and neck cancer is one of the most prevalent cancers around the world. Head and neck squamous cell carcinoma (HNSCC) accounts for nearly 90% of head and neck cancer. In recent years, significant advances have been made in immunotherapy for HNSCC. Although some clinical trials targeting immune checkpoints have shown success, the molecular mechanism for regulation of programmed death 1 (PD-1) and its ligand (PD-L1) is partially understood. In an effort to explore the effect of activation of signal transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 37 publications
6
117
0
1
Order By: Relevance
“…Because we observed that EGF induced IRF‐1 (Figures D and E), we ascertained that EGFR induced not only STAT1 but also IRF‐1 expression to increase the PD‐L1 level in selected EGFR‐positive cancers. EGFR can phosphorylate STAT3, which has been reported to determine the expression of PD‐L1; therefore, we speculated that EGFR‐STAT3 mediated the expression of STAT1 and IRF‐1 that was evaluated in this study (Figure G).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Because we observed that EGF induced IRF‐1 (Figures D and E), we ascertained that EGFR induced not only STAT1 but also IRF‐1 expression to increase the PD‐L1 level in selected EGFR‐positive cancers. EGFR can phosphorylate STAT3, which has been reported to determine the expression of PD‐L1; therefore, we speculated that EGFR‐STAT3 mediated the expression of STAT1 and IRF‐1 that was evaluated in this study (Figure G).…”
Section: Discussionmentioning
confidence: 82%
“…These findings indicate that phosphorylated STAT1 was derived from the IFNr‐JAK1/JAK2 signaling axis to determine PD‐L1 expression, whereas EGF exacerbated PD‐L1 expression by increasing the protein levels of STAT1. Since EGFR‐STAT3 has been documented participating in cancer stemness and inducing PD‐L1 expression, we then knockdowned and inhibited STAT3 in A549 cells by shRNA technique and BBI608, a STAT3 inhibitor, respectively. We found decreased expression of STAT1, IRF‐1, and PD‐L1 in A549shSTAT3 cells compared to that in A549shLuc cells (Figure G).…”
Section: Resultsmentioning
confidence: 99%
“…[ lymphoma (Marzec et al, 2008;Atsaves et al, 2017), melanoma (Jiang et al, 2013), HNSCC (Bu et al, 2017) RELA [ primary monocytes (Huang et al, 2013), melanoma (Gowrishankar et al, 2015), NSCLC (Bouillez et al, 2017), breast cancer (Xue et al, 2017) MUC1-C [ NSCLC (Bouillez et al, 2017) JUN [ lymphoma (Green et al, 2012), melanoma (Jiang et al, 2013) CDK5…”
Section: Stat3mentioning
confidence: 99%
“…It has been shown that increased JAK2 upregulates STAT1 but not STAT3 in HNSCC cell lines, resulting in increased PD‐L1 (Concha‐Benavente et al, ). Another study in a different HNSCC cell line (CAL27) found that blockade of STAT3 produced the loss of PD‐L1 overexpression (Bu et al, ). These contrasting results illustrate the importance of different JAK/STAT pathways in distinct HNSCC cell lines.…”
Section: Pd‐l1 In Cancermentioning
confidence: 99%